Pear drying: Perspectives for convective drying. - Guiné, Raquel (2007)
The present study aimed the evaluation of the possibilities of introducing alterations in the method used traditionally to dry pears in Portugal, by direct open-air sun exposure, in order to modernize it, making it possible to be used in an industrial scale, being more profitable and allowing the obtaining of dried pears with a better quality.